Răspuns: a = 3
Explicație pas cu pas:
88 - 70 × [ 60 - 5 × ( 132 : 4 - 63 : a ) + 1 ] - 6 = 12
88 - 70 × [ 60 - 5 × ( 33 - 63 : a ) + 1 ] = 12 + 6
70 × [ 60 - 5 × ( 33 - 63 : a ) + 1 ] = 88 - 18
70 × [ 60 - 5 × ( 33 - 63 : a ) + 1 ] = 70
60 - 5 × ( 33 - 63 : a ) + 1 = 70 : 70
60 - 5 × ( 33 - 63 : a ) + 1 = 1
60 - 5 × ( 33 - 63 : a ) = 1 - 1
5 × ( 33 - 63 : a ) = 60 - 0
5 × ( 33 - 63 : a ) = 60
33 - 63 : a = 60 : 5
33 - 63 : a = 12
63 : a = 33 - 12
63 : a = 21
a = 63 : 21
a = 3 -> numarul, aflat prin metoda mersului invers